Synergisms of Microbial Consortia, N Forms, and Micronutrients Alleviate Oxidative Damage and Stimulate Hormonal Cold Stress Adaptations in Maize - Moradtalab, Narges; Ahmed, Aneesh; Geistlinger, Joerg; Walker, Frank; Höglinger, Birgit; Ludewig, Uwe; Neumann, Günter (Frontiers in Plant Science, 2020)
Aims: Low soil temperature in spring is a major constraint for the cultivation of tropical crops in temperate climates. This study aims at the exploitation of synergistic interactions of micronutrients, consortia of plant growth-promoting microorganisms and N forms as cold-stress protectants. Methods: Maize seedlings were exposed for two weeks to low root zone temperatures at 8-14 °C under controlled conditions on a silty clay-loam soil (pH 6.9) collected from a maize field cultivation site. A pre-selection trial with fungal and bacterial PGPM strains revealed superior cold-protective performance for a microbial consortium of Trichoderma harzianum OMG16 and Bacillus spp. with Zn/Mn supplementation (CombiA+), particularly combined with N-ammonium as a starting point for the characterization of the underlying physiological and molecular mechanisms. Results: In maize nitrate-treated plants, the cold stress treatment increased oxidative leaf damage by 133% and reduced the shoot biomass by 25%, explained by the reduced acquisition of phosphate (P), zinc (Zn) and manganese (Mn). The supplying of N as ammonium improved the Zn and Mn maize nutritional status and increased the ABA shoot concentration by 33%, as well as moderately increased detoxification of reactive oxygen species (ROS). Moreover, use of N as ammonium also increased the root auxin (IAA) concentration (+76%), with increased expression of auxin-responsive genes, involved in IAA synthesis (ZmTSA), transport (ZmPIN1a), and perception (ZmARF12). Additional inoculation with the microbial consortium promoted root colonization with the inoculant strain T. harzianum OMG16 in combination with ammonium fertilization (+140%). An increased ABA/cytokinin ratio and increased concentrations of jasmonic (JA) and salicylic acids (SA) were related to a further increase in enzymatic and non-enzymatic ROS detoxification. Additional supplementation with Zn and Mn further increased shoot IAA, root length and total antioxidants, resulting in the highest shoot biomass production and the lowest leaf damage by oxidative chemical species. Conclusions: Our results suggest the mitigation of cold stress and reduction of stress priming effects on maize plants due to improved ROS detoxification and induction of hormonal stress adaptations rely on the strategic combination of stress-protective nutrients with selected microbial inoculants.